Endodermal cell-cell contact is required for the spatial control of Casparian band development in Arabidopsis thaliana. - Martinka, M; Dolan, L; Pernas, M; Abe, J; Lux, A (2012)
BACKGROUND AND AIMS: Apoplasmic barriers in plants fulfil important roles such as the control of apoplasmic movement of substances and the protection against invasion of pathogens. The aim of this study was to describe the development of apoplasmic barriers (Casparian bands and suberin lamellae) in endodermal cells of Arabidopsis thaliana primary root and during lateral root initiation. METHODS: Modifications of the endodermal cell walls in roots of wild-type Landsberg erecta (Ler) and mutants with defective endodermal development - scarecrow-3 (scr-3) and shortroot (shr) - of A. thaliana plants were characterized by light, fluorescent, confocal laser scanning, transmission and cryo-scanning electron microscopy. KEY RESULTS: In wild-type plant roots Casparian bands initiate at approx. 1600 µm from the root cap junction and suberin lamellae first appear on the inner primary cell walls at approx. 7000-8000 µm from the root apex in the region of developing lateral root primordia. When a single cell replaces a pair of endodermal and cortical cells in the scr-3 mutant, Casparian band-like material is deposited ectopically at the junction between this 'cortical' cell and adjacent pericycle cells. Shr mutant roots with an undeveloped endodermis deposit Casparian band-like material in patches in the middle lamellae of cells of the vascular cylinder. Endodermal cells in the vicinity of developing lateral root primordia develop suberin lamellae earlier, and these are thicker, compared wih the neighbouring endodermal cells. Protruding primordia are protected by an endodermal pocket covered by suberin lamellae. CONCLUSIONS: The data suggest that endodermal cell-cell contact is required for the spatial control of Casparian band development. Additionally, the endodermal cells form a collet (collar) of short cells covered by a thick suberin layer at the base of lateral root, which may serve as a barrier constituting a 'safety zone' protecting the vascular cylinder against uncontrolled movement of water, solutes or various pathogens.